Innovation in Fare Payment Systems for Public Transport in African Cities - Arroyo Arroyo, Fatima; Van Ryneveld, Philip Clive; Finn, Brendan; Greenwood, Karin Chantal; Coetzee, Gerhardus Koch (Washington, DC, 2022)
This study of African fare payment systems seeks to understand the emerging payment landscape in public transport in Sub-Saharan Africa, identifying key trends and their implications. The research draws on case studies undertaken in five African cities—Cape Town,Kigali, Lagos, Maputo and Nairobi—selected to cover a variety of contexts, innovations and language regions. A sixth case is included from India, identified through a wider international scan and which embodies some significant innovations relevant to the African context.